2006
DOI: 10.1016/j.ejheart.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of levosimendan infusion on inflammatory processes and sFas in patients with severe heart failure

Abstract: Background: The calcium sensitizer levosimendan improves myocardial contractility in patients with heart failure, although its effects on inflammation and apoptosis are unknown. Aim: To examine the effects of levosimendan on markers of inflammation and apoptosis, over a period of 30 d following a 24 h infusion, in patients with heart failure. Methods: Thirty four patients with severe heart failure were randomised to receive a 24 h infusion of levosimendan or placebo, in a doubleblind trial. Haemodynamic evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 32 publications
1
23
1
6
Order By: Relevance
“…Enhancing the calcium sensitivity of the contractile proteins and phos- phodiesterase III inhibition are believed to contribute to the LS-induced positive inotropic action (Edes et al, 1995;Haikala and Linden, 1995;Endoh, 2002). Activation of ATPdependent potassium channels in vascular smooth muscle cells and mitochondrial membranes (Yokoshiki et al, 1997a,b;Kaheinen et al, 2001) as well as recent demonstrated actions of LS, such as increased activity of the Na ϩ -Ca 2ϩ exchanger (Hasenfuss et al, 1998) and anti-ischemic (Moiseyev et al, 2002;Avgeropoulou et al, 2005), anti-inflammatory, and antiapoptotic properties (Follath et al, 2002;Parissis et al, 2004;Trikas et al, 2006) may also contribute to the dose-related enhancements of LV contractile performance and relaxation. Our findings are supported by evidence in vitro indicating that LS accelerates and does not impair relaxation in isolated cardiac muscle from endstage failing human hearts (Hasenfuss et al, 1998) and by a most recent clinical combined hemodynamic and Doppler echocardiographic study in severe HF patients.…”
Section: Dose-related Effect Of Oral Ls On Hemodynamic and LV Functiomentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancing the calcium sensitivity of the contractile proteins and phos- phodiesterase III inhibition are believed to contribute to the LS-induced positive inotropic action (Edes et al, 1995;Haikala and Linden, 1995;Endoh, 2002). Activation of ATPdependent potassium channels in vascular smooth muscle cells and mitochondrial membranes (Yokoshiki et al, 1997a,b;Kaheinen et al, 2001) as well as recent demonstrated actions of LS, such as increased activity of the Na ϩ -Ca 2ϩ exchanger (Hasenfuss et al, 1998) and anti-ischemic (Moiseyev et al, 2002;Avgeropoulou et al, 2005), anti-inflammatory, and antiapoptotic properties (Follath et al, 2002;Parissis et al, 2004;Trikas et al, 2006) may also contribute to the dose-related enhancements of LV contractile performance and relaxation. Our findings are supported by evidence in vitro indicating that LS accelerates and does not impair relaxation in isolated cardiac muscle from endstage failing human hearts (Hasenfuss et al, 1998) and by a most recent clinical combined hemodynamic and Doppler echocardiographic study in severe HF patients.…”
Section: Dose-related Effect Of Oral Ls On Hemodynamic and LV Functiomentioning
confidence: 99%
“…In contrast to dobutamine, LS does not increase myocardial oxygen demand and has anti-ischemic and antiarrhythmic actions (Pagel et al, 1997;Ukkonen et al, 2000;Moiseyev et al, 2002;Avgeropoulou et al, 2005). In patients with severe HF, LS exerts anti-inflammatory and antiapoptotic properties (Follath et al, 2002;Parissis et al, 2004;Trikas et al, 2006). Compared with dobutamine, LS demonstrated superior hemodynamic improvement and safety for treatment of acute, decompensated HF (Follath et al, 2002) and myocardial infarction complicated by LV dysfunction and HF.…”
mentioning
confidence: 99%
“…Levosimendan tedavisine bağlı BNP, NT-proBNP, IL-6, TNF-α düzeylerinde anlamlı azalma olduğu gösteril-miştir (12)(13)(14)(15). Çavuşoğlu ve ark.…”
Section: Discussionunclassified
“…(8)(9)(10)(11). Daha önce yapılan çalışmalarda, levosimendanın IL-6 ve TNF-α gibi proinflamatuar sitokin düzeylerini azalttığı gösterilmiştir (12,13). Bu çalışmada, ileri kalp yetersizliği hastalarında pozitif inotropi amacıyla kullanı-lan proinflamtuar sitokinler üzerinde olumlu yönde etkisi olduğu bildirilmiş olan levosimendan tedavisinin, kronik inflamasyonun bir göstergesi olan hemogram parametrelerinden RDW ve ekokardiyografik parametreler üzerin-deki etkilerinin araştırılması amaçlandı.…”
Section: Genel Tıp Dergisiunclassified
“…Levosimendan also exhibits neurohormonal and anti-inflammatory effects, reducing brain natriuretic peptide (BNP) level, as well as tumor necrosis factor alfa (TNF-α), interleukin-6 (IL-6), and proapoptotic factors sFas and Fas-ligand levels [29][30][31][32]. In addition, levosimendan improves both right ventricular function [33] and endothelial function, and has a beneficial effect on coronary blood flow [34,35].…”
Section: Levosimendanmentioning
confidence: 99%